Proposed Correlation for Gas solubility at and below Bubble Point Pressure - Mohammed M. Daway (Engineering and Technology Journal, 2014)
A study has been done to get an accurate correlation for solution gas-oil ratio (gas solubility). Two hundred and nine measured values from an Iraqi oil field have been used in this study. Many formulas are tested to get the best correlation for gas solubility. Every formula predicts the value of gas-oil ratio at any given pressure, temperature, oil density and gas specific gravity. Based on the nonlinear regression analysis, the constants of these formulas are determined. The formula with the minimum average absolute error among the assumed (reported an absolute average error of 4.97 % and a standard deviation of 453) is selected to be the proposed correlation for this study. The accuracy of the proposed correlation is assessed through a statistical test and compared with those achieved for some published correlations. This test shows that the proposed correlation has the best fitting with the experimental data. Cross plot technique is also applied to check the performance of the correlation which gave the same index of the statistical criterion method. Another method has been used to ensure the accuracy of the proposed correlation, in which a sample of external data (which is not used to develop the correlation) is tested. The results show the same index of the other methods